Penguatan Kualitas Pembelajaran Melalui Program Pengabdian di SMP Negeri Gampong Blang Crok Nisam - Rahmat; Zulfikar; Nuriman; Amrullah; Dina Handayani; Fauzi (Jurnal Solusi Masyarakat (JSM), 2026)
Strengthening the quality of learning at the junior high school level is an important priority in improving educational quality, particularly in rural areas. SMP Negeri Gampong Blang Crok in Nisam District is one of the schools facing challenges such as limited teacher competence in the use of digital learning media, active learning approaches, planning instructional tools aligned with the Merdeka Curriculum, and a lack of variation in teaching methods. This community service program aims to enhance teachers’ pedagogical and professional competencies, enrich instructional strategies, strengthen classroom management, and encourage student learning participation. The program employed participatory approaches, capacity building, lesson study, and performance-based evaluation. The results indicate a significant improvement in teachers’ ability to design differentiated learning, utilize ICT-based media (Canva, PowerPoint, educational videos), and increase student engagement in the learning process. This article presents a comprehensive overview of the program’s planning, implementation, outcomes, and recommendations for sustainable development.